The Wedding Code in Incantations - Vukmanović, Ana (Poznańskie Studia Slawistyczne, 2012)
Incantations use the wedding code in order to fulfill the magical function which faces a cure or a protection, demanded by certain people. Thus the wedding code applied to the incantation turns out to be different from the wedding song itself. The phenomena of anti-speech (insults directed to the bride or to the wedding guests) and of inverse reality of the sacred moment in the incantations become the powerful means against diseases and evil spirits. While modulating the wedding ritual objects (wedding shirt, wreath, veil, flag), or ritual actions (giving gifts, repulsing the wedding guests, taking the bride away from her parents’ house), these objects and acts gain a secondary, magical function that makes diseases and evil spirits drive away. The wedding songs and the incantations share the same model of space in which forest and water introduce themselves as the strong boundaries between two worlds: of the living and of the dead. While in the first case the boundaries are porous, allowing an interpenetration of both the worlds, inthe second one they remain closed off. The above mentioned genres also share some motifs –of a fast growing girl, hospitality (as well as of an uninvited guest) and magical counting. Furthermore, the article proves that various functions determine essentially different meanings of motifs, ritual actions and eventually characters which appear in these folklore genres.